Two new species of the genus Orizabus Fairmaire (Coleoptera: Scarabaeidae: Dynastinae) from southern and central Mexico - Morón, Miguel Angel; Tapia, Ana María; Aragón, Agustín (Zootaxa, 2003)
Two new Mexican species, Orizabus vulcanicus sp. nov. from Iztaccihuatl volcano (Puebla) and Orizabus dechambrei sp. nov. from the Omilteme mountains (Guerrero), are described. Drawings of the diagnostic structures of the new species and a key to the 14 species now included in the genus are provided.